Petunjuk pembangunan komuniti orang Asli: suatu analisis penggunaan barangan dan perkhidmatan - Rosnon, Mohd Roslan; Gill, Sarjit S.; Zainal Badari, Shamsul Azahari; W Ab Rahman, N Alia Fahada; Hafiz Goh, Adam Danial (Universiti Kebangsaan Malaysia. Fakulti Sains Sosial dan Kemanusiaan, 2019)
Modernization has, to some extent, affected the lives of indigenous peoples and exposed them to the current consumer world. The improved living standards and social changes have caused the consumption expenditure pattern on goods and services and the values of consumerism to change over time. Hence, this research aims to explain the use of goods and services, as well as the changes in values among orang Asli as a sign of community development. A total of 325 orang Asli from entire orang Asli settlement in Jelebu are involved in this research. The methods used are by doing reviews using questionnaire and also non-participant observations. The result is analysed descriptively. The result of the study shows that the orang Asli community has started using the modern goods and services. The changes in traditional to modern values has started to make its way into this community. In a nutshell the development has changed the life of orang Asli by looking at the use of modern goods and services as a manifestation in determining the acceptance of orang Asli community to modernization. The implications that can be seen are the changes of traditional toward modern values among orang Asli community and they have accepted modern goods and services. Hence, knowledge and education on the consumerism should be provided to the orang Asli community so that they will not be the victims of hedonism of the modern world of luxury brought about by modernization.